Static tensile test of materials - Li, Xiaopeng (Nanyang Technological University, 2021)
This Final Year Project (FYP) is about Aluminium 6061-T6 research and experimentation. The static tensile test is carried out on the test sample, and the outcome is compared with prior FYP reports and other related studies. The objective of this report is to comprehend the ASTM Standard and the static tensile test literature review. The aim of this study is to provide future reference in regards with the static tensile test on aluminium 6061-T6. Static tensile test is performed to calculate main mechanical properties of a sample material. Yield strength, ultimate strength, elongation at fracture and Young’s modules are the main mechanical properties. Shimadzu AGX plus 10kN was used in this FYP to perform the static tensile test on every sample. Each specimen stress- strain curve of Aluminum 6061-T6 will be plotted using the raw data derived from each test result. By comparing them to the result of the previous year student, further research on the curve will be analyzed. The aim of this project is to manufacture specimen for tensile testing by following the ASTM standard. The experiment aims to determine the difference between the specimen in the longitudinal and transverse direction. Different grain structure in different specimen directions could affect a material’s mechanical properties. For ease of comparison, the feed rate of 1.6 mm/min would be used as stated in ASTM in the experiment. The study will adjust to any developments and needs accordingly. As assistance to future reference, validation and procedures used in this study will be specified within the report. The author will provide a comprehensive guide for this project. The guide aims to provide transparency of the experiment procedures in achieving a more detailed and reliable outcome.